Effects of horizontal seismic band on seismic response in masonry structure: Application of DIC technique. (April 2021) - Yadav, Santosh; Damerji, Hala; Keco, Reinold; Sieffert, Yannick; Crété, Eugénie; Vieux-Champagne, Florent; Garnier, Philippe; Malecot, Yann
Abstract: Masonry construction is one of the oldest building systems and practiced since the early stage of human civilization. Even though industrialized nations developed new building practices using steel and concrete materials, most developing countries still use unreinforced masonry buildings. Evidence from past events shows that masonry structures sometimes performed well and survived several earthquake events, particularly in the area where earthquake events struck regularly and enough to show how structures behave. However, an alteration from the traditional cultural building practice is seen due to the lack of proper scientific knowledge about such local construction cultures. Amongst traditional construction technics, one captured authorities' and scientists' attention as showing excellent properties: seismic bands that can be found in many parts of Nepal. After the 2015 Gorkha earthquake, reconstruction works started adopting the guidelines developed by DUDBC and National Building code that suggest using such seismic bands. The evidence of using such band dates to 2500 BCE, and qualitative studies of those applications have proven to enhance the performance in the masonry structure. However, the experiment's quantitative parameters using various materials are needed to carry out the parametrical analysis to optimize seismic band's use. To provide quantitative results, we have started with two specimens, one without a band and one with a timber seismic band, and incorporate the digital image correlation (DIC) technique to obtain the localized information. The quasi-static cyclic test is carried out for our specimens to compare the behavior concerning the energy dissipation, and the surface area of the crack formed during the loading cyclic. This work clearly shows the seismic band's advantage in limiting the crack propagation and improving masonry structure integrity. Highlights: Seismic band for earthquake resistance house. Traditional construction technique. Application of Digital Image Correlation technique. In-plane quasi-static cyclic test.